Islamic Banking Stability: A Bibliometric Analysis - Adnan, Muhammad Ichsan; Majid, M. Shabri Abd; Gunawan, Eddy (Falah: Jurnal Ekonomi Syariah, 2024)
The rapid evolvement and higher stability of Islamic banking institutions across the global Muslim world as compared to their conventional banking industry has attracted more researchers to explore Islamic banks as one of the viable financial institutions to the existing unstable global financial system. This study intends to analyze descriptively the trends of research on the theme of Islamic banking stability. This study using bibliometrics analysis collected from published articles in international reputable journals indexed in the Scopus database over the period from 2010 to 2020. To analyze the selected articles used VOSviewer software and microsoft excel spreadsheet from publish and perish database using the keywords of Islamic bank, bank stability, and Islamic banking stability. The result found that there were an increasing number of articles published on the topic. This study recorded 175 articles on the topic, authorized by 149 authors from different countries, and published in 103 international reputable journals. These findings showed that the topic of Islamic banking stability has become one of the important issues of global financial stability. This study contributes to the field of Islamic finance by mapping the existing studies on the Islamic banking stability and enrich the literature in the discourse of Islamic banking stability.